The Influence of Electronic Word-of-Mouth on Consumers’ Purchase Intentions and Brand Awareness in Iranian Telecommunication Industry - Yousef Sharifpour; Mohd Noor Azli Ali Khan; Mostafa Alizadeh; Mohammad Rahim Akhgarzadeh; Edris Mahmodi (International Journal of Supply Chain Management, 2016)
Electronic word of mouth (eWOM) is an emerging marketing experience for consumers which impacts their assessment of different existing brands and products such as mobile brands through online communication channels. This study aims to explain the effect of Word of mouth on purchase intention and brand awareness focusing on Samsung cellphone brand. The group studied in the current work is a sample of Samsung customers in Esfahan city in Iran (2015). In this study, for the sake of data collection, a form of descriptive research method is applied. The Statistical sample consists of 384 respondents who accepted to take the survey which was prepared in the form of a questionnaire. According to result analysis, the study showed that there is a significant positive relationship between the electronic word of mouth and purchase intention and there is a significant positive relationship between the awareness of a brand and purchase intention while there was no effective relation found between electronic word of mouth and brand awareness. Base on this, out of the three proposed hypothesis two hypothesis are accepted and one hypothesis is not denied. Keywords: electronic word of mouth, purchase intention, Brand awareness